Mechanics and failure characteristics of hybrid fiber-reinforced concrete (HyFRC) composites with longitudinal steel reinforcement. (15th March 2019) - Nguyen, Wilson; Bandelt, Matthew J.; Trono, William; Billington, Sarah L.; Ostertag, Claudia P.
Graphical abstract: Highlights: The direct tensile response of reinforced HyFRC (R/HyFRC) is investigated. R/HyFRC strengthening is dependent on strain-hardening rebar and softening HyFRC. Rebar reinforcement ratio and fiber type can affect R/HyFRC strengthening. Single dominant crack localization occurs in R/HyFRC at low reinforcement ratio. R/HyFRC has greater tensile load capacity and lower strain capacity than R/C. Abstract: While the properties of hybrid fiber-reinforced concrete (HyFRC) have been well-reported in the literature, the behavior of reinforced HyFRC (i.e., HyFRC with embedded steel rebar) is less understood. This paper investigates the mechanics and failure characteristics of reinforced HyFRC under direct tension. Samples with a low longitudinal steel reinforcement ratio were studied to evaluate the feasibility of reducing rebar congestion in structural applications through the use of fiber-reinforced concrete. Although reinforced HyFRC forms multiple cracking sites when loaded, rebar strain and HyFRC crack opening are generally concentrated at a single location under post-yield displacements. The onset of rebar plastic deformation and the exhaustion of fibers' bridging load capacity are coincident events at a dominant crack. For a cracked reinforced HyFRC section to strengthen, the magnitude of load resistance increase from strain hardening rebar must exceed the magnitude of load resistance decrease from fiber pull-out processes. Comparisons are made with studies reported in the literature to demonstrate how longitudinal reinforcement ratio and fiber type influence cracking behavior and ultimate strain capacity. The research presented herein has far-reaching impacts on the structural design of all types of reinforced fiber-reinforced concrete materials detailed for a ductile response under large displacements.